Evaluating Pollutants of Emerging Concern in Aquatic Media Through E-PRTR Regulation. A Case Study: Cordoba, Spain, 2009-2018 - Marin Galvin, R. (Engineering, Technology & Applied Science Research, 2019)
The E-PRTR EU Regulation can be followed for the evaluation of the level of pollutants of emerging concern in treated wastewater. This regulation is of regional responsibility in the UE, and establishes for the Andalusian region of Spain the following pollution parameters as mandatory to be controlled periodically in treated wastewater in Waste Water Treatment Plants (WWTPs) with more than 100.000 equivalent inhabitants of treatment capacity: COD, N-Kjeldahl, total P, Cl-, F- (conventional pollution); As, Cd, Cr, Cu, Hg, Ni, Zn and Pb, as heavy metals; PAHs (polycyclic aromatic hydrocarbons), adsorbed organic halides (AOXs), benzene and chloroform, as organic compounds. This paper shows results obtained in the application of the E-PRTR Regulation to the wastewater of Cordoba during 2009-2018. As shown, average of COD, N-Kjeldahl an total P values, respectively, in urban and treated wastewater were 604 and 89 mg/L, 54.1 and 33.4 mg/L and 3.4 and 1.4 mg/L. With respect to heavy metals, the mean content in treated wastewater was 0.135 mg/L, starting from 0.226 mg/L in raw wastewater. The majority of these are Cu and Zn (0.043 mg/L and 0.107 mg/L, respectively, in raw wastewater). For pollutants of emerging concern, the mean content of PAHs was 13 ng/L in treated water vs 31 ng/L in raw wastewater. Moreover, concentration of AOXs in raw wastewater was of 20 ng/L while in treated wastewater decreased up to 16 ng/L. Also, benzene content in raw wastewater and treated wastewater decreased from 40 ng/L to 11 ng/L. Finally, the major organic compound was chloroform, with a level in raw wastewater of 5.6 ng/L that was reduced along the treatment up to 3.2 ng/L. The provided data indicated a low concentration of the compounds of emerging concern in the wastewater of Cordoba and its minimal impact on the receiving aquatic environment (the Guadalquivir river).